ANALISIS PELAKSANAAN KESELAMATAN PASIEN TERKAIT AKREDITASI DI PUSKESMAS (LITERATURE REVIEW) - Bernadeta Lintang Hardy; Sutopo Patria Jati; Yuliani Setyaningsih (Dian Nuswantoro Semarang, 2023)
Puskesmas as a first-level health facility must improve the quality of health services to the maximum so that the accreditation status increases and public trust to carry out health services also increases. One of the important indicators in improving the quality of health services at Puskesmas is patient safety. However, in Indonesia, the development of issues regarding patient safety at the Puskesmas level is not as dynamic as at the hospital level. This study aims to dig deeper and synthesize the scientific literature on patient safety and its relation to accreditation in health centers. This review uses 2 databases namely Google Scholar and Garuda. The main keywords are